2012
DOI: 10.2298/pif1204305g
|View full text |Cite
|
Sign up to set email alerts
|

Antifeeding activity of several plant extracts against Lymantria dispar L. (Lepidoptera: Lymantriidae) larvae

Abstract: SUMMARYLymantria dispar L. is the most devastating polyphagous pest of deciduous forests, orchards and urban greenery. To prevent damages that L. dispar larvae cause in forestry, agriculture and horticulture, mechanical measures and the use of biological insecticides are the most frequently applied practices. However, the use of conventional insecticides is inevitable in crop protection and forest management on smaller areas, especially in gradation years. However, inadequate use of these chemicals has led to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
1
5
0
1
Order By: Relevance
“…The extract of M. alba leaves exhibited strong antifeeding effect, which is in accordance with the results of previous research of Gvozdenac et al (2012). Antifeeding activity can be attributed to kaemferol, 2 hidroxycinnamic and caffeic acid and quercetin detected in the extract.…”
Section: Conclusion and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The extract of M. alba leaves exhibited strong antifeeding effect, which is in accordance with the results of previous research of Gvozdenac et al (2012). Antifeeding activity can be attributed to kaemferol, 2 hidroxycinnamic and caffeic acid and quercetin detected in the extract.…”
Section: Conclusion and Discussionsupporting
confidence: 91%
“…Plants are a rich source of compounds that exhibit high biological activity against harmful insects, thus botanical preparations are good potential substitutes for synthetic insecticides in agricultural and forest pest control (Bohinc et al, 2020;Šućur et al, 2015;Hikal, Baeshen & Said-Al Ahl, 2017;Gvozdenac, Šućur, Manojlović, Prvulović & Malenčić, 2018). In recent years, antifeeding effects of various plants and plant extracts have been studied for gypsy moth larvae and several findings confirm the antifeedant or repellent activity of Pinus taeda L., Juniperus virginiana L., Acer rubrum L. (Keena & Richards, 2020), Ocimum basilicum L. (Kostić et al, 2008;Popović et al, 2013), Morus alba L. and Aesculus hippocastanum L. (Gvozdenac, Inđić, Vuković, Grahovac & Tanasković, 2012). Botanical insecticides have many advantages, primarily low toxicity and selectivity towards non-target, and high toxicity to target organisms and also the capacity to avoid the occurrence of insect resistance and biodegradability (Kostić et al, 2008;Krinski, Massaroli & Machado, 2014).…”
Section: Introductionmentioning
confidence: 78%
“…and Rosmarinus officinalis L. [ 70 , 74 , 75 , 76 ]. The antifeeding activity of anise EO is similar to that of ethanolic leaf extracts of Aesculus hyppocastanum L. and Morus alba L. [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results coincided with Chennaiyan et al [71] stated that Barleria longiflora leaves affect the S. litura larvae feeding behavior. Gvozdenac et al [72] observed that Aesculus hippocastanum had a highly antifeeding activity against Lymantria dispar larvae. However, Ambrosia artemisiifolia, Daucus carota, and Elodea canadensis exhibited no antifeedant activity.…”
Section: Toxicity Effects Of the Tested Bos On The Nutritional Indices Of A Ipsilonmentioning
confidence: 99%